(untitled) (Filološke studije, 2019)
From the philosophical point of view three mode of time can be distinguished: circular, linear and «eternal» time. In our Western cultural tradition the linear (or historical, eschatological) time became the dominant modus with Christianity, and step by step it has been modified into the evolutionary time of modern science, in ancient pagan cultures, especially Greek and Roman, time was conceived as essentially circular (or cyclic), renewed again and again in myths and rituals. However, from antiquity to modern times there is the third modus of time, present in the works and thoughts of mystics, seers and poets, time which can be considered as «eternal», nuns stans (standing now) and compared with the point in the middle of the circle or a point anywhere on a line – this third modus of time is the main topic of this paper.